The price consequences of diversification of regional development in Poland - Przekota, Grzegorz; Lisowska, Agnieszka (Management and Administration Journal, 2020)
The economic potential of individual regions of Poland is different. Each region has its own individual specificity. Use of the specific nature of a given region is a significant element of managing the country as a whole and individual regions. Occurring imbalances in economic development may cause a lot of adverse conditions, such as internal migration or regional marginalisation. Excessive price and income disparities may consequently result in under mining the economic growth of the entire country. For reason of coherence of the whole country, it is beneficial if disproportions between given regions are not too large. This study focuses on an attempt to identify the price consequences of diversification of regional development in Poland. The analysis drew on coefficient of variation, correlation coefficient, regression coefficient and medium-term rate. It is noted that individual regions are different in terms of the dynamics of economic growth, degree of development and salary level. However, prices are much less diverse.